2013
DOI: 10.1097/aud.0b013e318272f189
|View full text |Cite
|
Sign up to set email alerts
|

Speech Perception With Combined Electric-Acoustic Stimulation and Bilateral Cochlear Implants in a Multisource Noise Field

Abstract: Combined EAS in one ear supported by a hearing aid on the contralateral ear provided significantly improved speech perception compared with bilateral cochlear implantation. Although the scores for monosyllable words in quiet were higher in the bilateral CI group, the EAS group performed better in different noise and sound field conditions. Furthermore, the results indicated that binaural interaction between EAS in one ear and residual acoustic hearing in the opposite ear enhances speech perception in complex n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
66
0
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(86 citation statements)
references
References 0 publications
8
66
0
12
Order By: Relevance
“…They hypothesized that the reduction in available F0 voicing cues makes sound source segregation difficult. Additional support for this hypothesis is found in studies of bimodal hearing in which the CI user has residual hearing in the non-implanted ear (Looi and Radford 2011;Rader et al 2013). The general finding of these studies is that the residual acoustic hearing improves both complex tone pitch perception as well as speech reception in noise even when the acoustic hearing does not provide sufficient cues for speech reception by itself.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…They hypothesized that the reduction in available F0 voicing cues makes sound source segregation difficult. Additional support for this hypothesis is found in studies of bimodal hearing in which the CI user has residual hearing in the non-implanted ear (Looi and Radford 2011;Rader et al 2013). The general finding of these studies is that the residual acoustic hearing improves both complex tone pitch perception as well as speech reception in noise even when the acoustic hearing does not provide sufficient cues for speech reception by itself.…”
Section: Introductionsupporting
confidence: 62%
“…While the magnitude of the observed masking release in temporally gated SSN was smaller for CI users (5.3 and 8.4 dB on consonant and vowel materials, respectively) compared to their normal hearing peers (13.3 and 18.2 dB on consonant and vowel materials, respectively), the fact that CI users do show some masking release in temporally gated SSN is promising. Other studies have generally found little or no masking release in temporally gated, or fluctuating, noise for CI users (Nelson et al 2003;Stickney et al 2004;Rader et al 2013). In fact, some evidence indicates an opposite phenomenon where CI users perform worse in the fluctuating noise condition (Kwon and Turner 2001;Nelson et al 2003;Stickney et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…better speech understanding in diffuse noise (Dorman and Gifford, 2010; Dunn et al, 2010; Gifford et al, 2010, 2013; Rader et al, 2013)…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have documented the efficacy of hearing preservation for significantly improving speech understanding in semi-diffuse noise (Dunn et al, 2010; Dorman and Gifford, 2010; Gifford et al, 2010, 2013; Rader et al, 2013) and reverberant speech (Gifford et al, 2013). Indeed, Gifford et al (2013) showed that some hearing preservation CI recipients had access to ITDs and that ITD thresholds for a 250-Hz signal were significantly correlated with the degree of speech recognition benefit afforded by the preserved hearing in the implanted ear.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, patients are left with the option of bimodal use (CI ipsilateral, HA opposite ear), but we would like to emphasize that the major goal should be to preserve acoustic hearing and leave the option for bilateral combined stimulation. This mode results in better scores in speech understanding under noisy conditions (10,11), and EAS patients outperform users of the bimodal mode when tested within a multisource noise field (12). It is therefore not reasonable to dismiss the idea of EAS in cochlear reimplantation.…”
Section: Discussionmentioning
confidence: 98%